Using data analytics to understand visitors online search interests: the case of Côa Museum - Carvalho, Aida (2020)
The Internet and more specifically the World Wide Web have revolutionized the tourism industry. Visitors can now search for substantial amounts of information about the tourism destinations that they wish or ponder visiting and, in this way, decide and plan their trips. This new paradigm generated numerous advantages for the tourist and constituted an empowerment in what concerns to its independence from the tourist agents. Through the trail of information that this process generates, the tourism industry has the possibility to know the interests of their putative clients before they even visit them. In this way, knowing the profile of interest of the visitors is now also an empowerment of the tourism industry as it starts to have tools that allow better understand the needs and expectations of visitors and, in this way, better manage their activities, converging to a more assertive and efficient business response. This article, supported by the fundamentals of Data Analytics and using the Google Trends tool, presents and discusses a study about the intersections of the Portuguese region of the Côa Valley and the Côa museum, in order to better understand the relations of interest between the region and one of his most prominent ex-libris. It was identified the most searched used keywords, distinguishing national and international tourists and, for these, characterizing their nationality.